For Derrida. - Miller, J. (Fordham University Press, 2009)
This book?the culmination of forty years of friendship between J. Hillis Miller and Jacques Derrida, during which Miller also closely followed all Derrida?s writings and seminars?is?for Derrida? in two senses. It is?for him,? dedicated to his memory. The chapters also speak, in acts of reading, as advocates for Derrida?s work. They focus especially on Derrida?s late work, including passages from the last, as yet unpublished, seminars. The chapters are?partial to Derrida,? on his side, taking his part, gratefully submitting themselves to the demand made by Derrida?s writings to be read?slowl.